Bibliometric Analysis of Parental Roles, Social Media Use, Digital Literacy Skills, and Moral Decadence - Safira Ainnur Faqih; Elly Malihah Setiadi; Wilodati Wilodati (Lembaga Riset Ilmiah, 2026)
This study aims to analyze the development of research on parental roles, social media use, digital literacy, and moral decadence through a bibliometric approach. Bibliographic data were retrieved from the Google Scholar database using the Publish or Perish application, covering publications published between 2020 and 2025. The dataset was selected by applying predefined inclusion and exclusion criteria to ensure the relevance and quality of the bibliographic records. The data were analyzed using VOSviewer through co-occurrence, network, overlay, density, co-authorship, and citation analyses. The results revealed three dominant research clusters: (1) parental roles and digital literacy, (2) media literacy and social media literacy, and (3) the relationship between social media and moral decadence. Overlay visualization indicated a shift in research trends from media literacy toward parental roles and digital literacy as preventive strategies to mitigate the negative impacts of social media. Density visualization identified digital literacy, role, and decline as the most frequently studied keywords. Co-authorship analysis showed that collaboration among researchers remains limited to relatively small research groups, while citation analysis identified the most influential studies as those addressing the impact of digital technology on cognitive development, digital ethics, and character formation. This study contributes to the literature by providing a comprehensive bibliometric mapping of the research landscape, identifying emerging themes, collaboration patterns, and future research directions to strengthen parental involvement and digital literacy in fostering healthy digital behavior and preventing moral decadence in the digital era.